2022
DOI: 10.3390/ijms23095107
|View full text |Cite
|
Sign up to set email alerts
|

Global Noncoding microRNA Profiling in Mice Infected with Partial Human Mouth Microbes (PAHMM) Using an Ecological Time-Sequential Polybacterial Periodontal Infection (ETSPPI) Model Reveals Sex-Specific Differential microRNA Expression

Abstract: Periodontitis (PD) is a polymicrobial dysbiotic immuno-inflammatory disease. It is more prevalent in males and has poorly understood pathogenic molecular mechanisms. Our primary objective was to characterize alterations in sex-specific microRNA (miRNA, miR) after periodontal bacterial infection. Using partial human mouth microbes (PAHMM) (Streptococcus gordonii, Fusobacterium nucleatum, Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia) in an ecological time-sequential polybacterial perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(61 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…We previously reported that the oral inoculation of Gram-negative subgingival periodontal bacteria ( P. gingivalis , T. denticola , or T. forsythia ) promotes bacterial colonization on the gingival surface and induces miRNA expression [ 19 , 23 , 25 , 30 , 31 ]. In the present study, new experiments were conducted designed to examine whether Gram-positive S. gordonii , inhabiting the supragingival region can colonize gingival epithelium and induce PD in mice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that the oral inoculation of Gram-negative subgingival periodontal bacteria ( P. gingivalis , T. denticola , or T. forsythia ) promotes bacterial colonization on the gingival surface and induces miRNA expression [ 19 , 23 , 25 , 30 , 31 ]. In the present study, new experiments were conducted designed to examine whether Gram-positive S. gordonii , inhabiting the supragingival region can colonize gingival epithelium and induce PD in mice.…”
Section: Resultsmentioning
confidence: 99%
“…The sex-specific DE miRNA reported in the partial human mouth microbes (PAMHH)- ETSPPI model that utilized five different bacteria including S. gordonii (early bacterial colonizer), F. nucleatum (intermediate bacterial colonizer), P. gingivalis, T. denticola and T. forsythia (late bacterial colonizers) using a time sequential infection [ 19 ]. Recently, we reported a polybacterial PD mouse model that induced miRNA expression, but the novelty of studying specific bacterium S. gordonii alone in inducing PD and specific miRNAs DE was not examined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations